2008
DOI: 10.1016/j.febslet.2008.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Targeting STAT1 by myricetin and delphinidin provides efficient protection of the heart from ischemia/reperfusion‐induced injury

Abstract: a b s t r a c tFlavonoids exhibit a variety of beneficial effects in cardiovascular diseases. Although their therapeutic properties have been attributed mainly to their antioxidant action, they have additional protective mechanisms such as inhibition of signal transducer and activator of transcription 1 (STAT1) activation. Here, we have investigated the cardioprotective mechanisms of strong antioxidant flavonoids such as quercetin, myricetin and delphinidin. Although all of them protect the heart from ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 33 publications
6
56
0
Order By: Relevance
“…However, recently novel protective mechanisms are arising, e.g. inhibition of signal transducer and activator of transcription 1 (STAT1) by anthocyanidin delphinidin [39], and others. Thus, modulation of heart functioning under conditions of increased oxidative stress must be ascribed to multilevel biologic activities of flavonoids, incorporating intracellular signal transduction cascades.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently novel protective mechanisms are arising, e.g. inhibition of signal transducer and activator of transcription 1 (STAT1) by anthocyanidin delphinidin [39], and others. Thus, modulation of heart functioning under conditions of increased oxidative stress must be ascribed to multilevel biologic activities of flavonoids, incorporating intracellular signal transduction cascades.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are reports that anthocyanins significantly inhibit TNFa-induced inflammation through monocyte chemoattractant protein-1 in human endothelium [67], suppress myocardial ischemia-reperfusion injury by delphinidin through the inhibition of signal transducers and activators of transcription 1 activity in cardiac muscle [68], and potentially inhibit the effects of C3G or its metabolite, protocatechuic acid, on atherosclerosis progression via inhibition of inflammation [69,70].…”
Section: Cvdmentioning
confidence: 99%
“…They have been shown to function as potent antioxidants and radical scavengers in vitro. Many studies have shown that increased dietary intake of flavonoid-rich foods decreases myocardial I/R injury in vivo (Hung et al, 2004;Ikizler et al, 2007;Toufektsian et al, 2008;Yamazaki et al, 2008), with many others showing protection by direct addition of flavonoids to the blood or perfusate in ex vivo isolated hearts (Amorini et al, 2003;Aneja et al, 2004;Fantinelli et al, 2005;Hirai et al, 2007;Scarabelli et al, 2009).…”
Section: Introductionmentioning
confidence: 99%